The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1111/famp.12752
|View full text |Cite
|
Sign up to set email alerts
|

The impact of responsible fatherhood programs on parenting, psychological well‐being, and financial outcomes: A randomized controlled trial

Abstract: The objective of this study was to examine differences in parenting, psychological well-being, and economic outcomes between fathers receiving two different programs offered by Fathers & Families Support Center for economically disadvantaged fathers: (a) Family Formation (FF), a 6-week/240-h program focused on economic stability/mobility, responsible fatherhood, and healthy rela-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Scholars have confirmed the influence of fathers’ presence on teenagers’ social responsibility. On the one hand, it has been shown that responsible fathers, who are involved in the development of children as male role models, contribute to the development of a sense of social responsibility in children ( Randles, 2020 ; Donnelly et al, 2022 ; Kohl et al, 2022 ). On the other hand, researchers found that absence of fathers may lead to teenagers’ depression, self-loathing, and impulsion and increase their probability of random sexual behavior, whereas casual sex reflected teenagers’ indifference to a sense of responsibility for marriage and love to a certain extent ( Liu, 2017 ; Hehman and Salmon, 2021 ).…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Scholars have confirmed the influence of fathers’ presence on teenagers’ social responsibility. On the one hand, it has been shown that responsible fathers, who are involved in the development of children as male role models, contribute to the development of a sense of social responsibility in children ( Randles, 2020 ; Donnelly et al, 2022 ; Kohl et al, 2022 ). On the other hand, researchers found that absence of fathers may lead to teenagers’ depression, self-loathing, and impulsion and increase their probability of random sexual behavior, whereas casual sex reflected teenagers’ indifference to a sense of responsibility for marriage and love to a certain extent ( Liu, 2017 ; Hehman and Salmon, 2021 ).…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Kohl et al, 2022 [20] ; Paoli et al, 2018 [22] ; Sherr, 2010 [21] While fathers can be biological or adoptive adult males, the essence of fatherhood lies in their overall reproductive potential, the likelihood of becoming parents, and their engagement in all facets of family life. Owing to the development of medicine, assisted reproductive technology (ART) has increased the chance of fatherhood for men.…”
Section: Psychologymentioning
confidence: 99%
“…(i) The status of father-child bonding A person enters fatherhood when becoming a father with or without blood connection [3,5,12,13,15,[20][21][22][23] . Although bonding with the child is a subjective feeling state of "love" for the child, father-child connection or relationships can be strengthened in this way [2,28] .…”
Section: Step 4: Determining the Defining Attributesmentioning
confidence: 99%
“…Despite the prevalence of fatherhood programs, evaluation of these programs is still in the early stages. There are some recently published studies of the efficacy of these programs in regard to improved economic stability and individual well-being of fathers, as well as more father involvement with their children and better coparenting relationship quality (e.g., Avellar et al 2018;Cowan, Cowan, and Gillette 2022;Holmes et al 2010;Kohl et al 2022;Peterson, Cramer, and Thompson 2022). A recent meta-analysis of 30 studies showed small average effects for improvement in father involvement and coparenting; however, across studies there were not significant effects for fathers' economic factors (Holmes et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of formative and summative evaluation studies will help to create more effective and successful program designs in the future and serve to inform efforts to develop models of practice. While efficacy studies can provide evidence of program impact by using random control assignment and determining trajectories of change for the average participant in comparison to nonparticipants (e.g., Cowan et al 2022; Kohl et al 2022), process evaluations provide information on factors that influence change among participants and their families. They also can provide more nuanced information useful for program directors and facilitators, particularly since a diverse group of fathers in various settings participate in programs with different designs.…”
Section: Introductionmentioning
confidence: 99%